The Aegean Archipelago as cradle: divergence of the glaphyrid genus Pygopleurus and phylogeography of P. foina. Issue 4 (19th May 2021) - Avtzis, Dimitrios N.; Markoudi, Vasiliki; Mizerakis, Vangelis; Devalez, Jelle; Nakas, Georgios; Poulakakis, Nikolaos; Petanidou, Theodora
Abstract : The genus Pygopleurus includes some of the most important beetle pollinators of the Eastern Mediterranean islands, showing a particular affinity to red-guild flowers. Focussing on the Aegean Archipelago, 75 individuals belonging to five Pygopleurus species were sampled and screened for two mtDNA loci (COI and 16S). The phylogenetic analysis implemented both by Bayesian and Maximum Likelihood approaches, showed a deep and robust structure for three species, mostly reflecting the palaeogeographic history of the islands. Interspecific divergence among them appears to have emerged at the beginning of the Messinian Salinity Crisis (5.99-5.33 Mya), with differentiation dating back to the eustatic sea level changes of the Pleistocene (2.56-0.0117 Mya). For P. foina, the most abundant species in the Aegean Archipelago, a finer sampling (121 individuals from 8 islands) and analysis of COI locus showed a distinct separation between northern and southern islands of East Aegean that disconnected non-simultaneously from the continent during the Pleistocene. A strong geographic structure was also evident at smaller taxonomic scales, with island populations exhibiting unique haplotypes. Thus, we concluded that the major palaeogeographic events of the region are reflected in the observed patterns of inter- and intraspecific divergence among and within Pygopleurus species in the Aegean Archipelago, something that is facilitated by this genus' low dispersal ability.